Analysis Of Reed Resource Dynamics In Water Bodies Of Eastern Latvia (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The paper shows the results obtained during the research of reed dynamics revealing that in Eastern Latvia 20 lakes and pisciculture farms are potentially important for the reed extraction. In 2008, the reed resources there covered a territory of approximately 2300 ha. The ortophoto images of potentially important water bodies made in 1997, 2005 and 2008 were analyzed using the computer program ArcMap. The reed growth develops differently in every water body, but in general the eutrophication of water bodies and the enlargement of reed-covered areas can be observed. The most rapidly the reed occupies new territories in pisciculture farms and shallow lakes. The analysis of reed resource dynamics show that reed-covered areas in this region are expanding every year. The main factors that influence the distribution of reed growths refer to human activities, climatic conditions, hydrological regime in water bodies and natural processes of eutrophication.